A new extra‐focus monochromator designed for high‐performance VUV beamlines. (3rd February 2015) - Xue, Chaofan; Wu, Yanqing; Zou, Ying; Xue, Lian; Wang, Yong; Xu, Zijian; Tai, Renzhong
<x xml:space="preserve">Abstract</x> A new monochromator called an extra‐focus constant‐included‐angle varied‐line‐spacing (VLS) cylindrical‐grating monochromator (extra‐focus CIA‐VCGM) is described. This monochromator is based on the Hettrick–Underwood scheme where the plane VLS grating is replaced by a cylindrical one in order to zero the defocus at three reference photon energies in the vacuum‐ultraviolet range. It has a simple mechanical structure and a fixed focus spot with high performance over a wide energy range. Furthermore, its mechanical compatibility with a standard VLS plane‐grating monochromator allows convenient extension into the soft‐X‐ray range.